Pengaruh Konsentrasi dan Lama Perendaman GA3 terhadap Perkecambahan Benih dan Pertumbuhan Bibit Johar (Cassia seamea) - Ahmad Yunus; Arifiya Qifni; Puji Harsono; Bambang Pujiasmanto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Johar (Cassia seamea) is a medicinal plant with a cassiarin A compound to combat malaria and has a low Cassiarin A is an active compound in Johar (Cassia seamea) medicinal plant capable of combating malaria, despite showing a low seed production rate due to dormancy. This inactivity is severed using gibberellic acid (GA3) treatments. This study aims to determine the effects of concentration and soaking period of GA3 on seed germination and growth of Johar seedlings. A completely randomized design (CRD), consisting of 2 treatments was applied as the research method. The first treatment employed GA3 concentrations of 0, 45, 90 and 135 ppm, while the second was based on the soaking interval at 6, 12, 18 and 24 hours. The results showed the capacity of GA3 able to shatter the seed dormancy with percentage germination of 43.03% and a concentration of 50.28 ppm. Therefore, the interaction of the two treatments significantly influenced the growth of Johar seedlings. Consequently, the concentration of GA3 at 79.89 ppm increased the root length to 52.19 cm, while 84.68 ppm produced a total of 20.91 roots, after a 6 hour soaking. In addition, the 96.67 ppm expanded the stem diameter by 0.93 cm.